Artificial Intelligence-Based Music as a Cultural Practice: A Socio-Anthropological Analysis of Creativity, Agency, and Algorithmic Mediation - Guna, Buky Wibawa Karya; Sjoraida, Diah Fatma; Reffali, Soni; Dipura, Agus Sukarna; Hidayah, Yuly (LP. Ma'arif Janggan Magetan, 2024)
The integration of artificial intelligence (AI) in music production is growing rapidly and has given rise to debates about creativity, authorship, and the role of human agents in cultural practices. While a number of previous studies have tended to highlight the technical, economic, or legal aspects of AI-based music, studies of its socio-anthropological implications are still limited. This research aims to analyze AI-generated music as a cultural practice that is at the intersection of human and machine agents. Using a qualitative socio-anthropological approach, this study applies digital ethnography and document analysis to AI music platforms, musical artifacts, and online public discussions that developed between 2022–2024. The findings show that AI-based music practices are characterized by the normalization of algorithmic sounds, increasing human-AI collaboration, unclear boundaries of authorship, the influence of algorithmic mediation on cultural visibility, as well as ambivalent listener responses. The results show that AI does not replace human creativity, but reconfigures music agencies through relational and curatorial practices shaped by the platform's infrastructure. The study concludes that AI-based music is a new socio-technical configuration in which creativity, meaning, and cultural authority are negotiated on an ongoing basis. The contribution of this research enriches the study of music anthropology, posthumanist theory, and critical discourse on cultural production in algorithmic societies.